Psychological Structure in the Poetry "Al-Khutwah Al- Akhirah" (Review of Psychological Analysis of Literature) - Cut Maya Husna (al-Afkar, Journal For Islamic Studies, 2024)
This study aimed to describe the form of psychoanalytic structure in the poem "Al-Khutwah Al-Akhirah" by Nazik Al-Malaikah with Sigmund Freud's psychoanalytic approach through the analysis of literary psychology theory. The research method used to reveal the form of psychoanalytic structure implied in the content of the sentence of Al-Khutwah Al-Akhirah poem is qualitative descriptive method. The research data found in the form of phrases, sentences, words, and discourse that show the personality structure contained in the poem. And based on the results of the analysis obtained from this study, namely about the form of psychoanalysis structure in the form of id, ego, and super ego.